Simultaneous Paranasal Augmentation and Le Fort I Osteotomy Using a Patient-Specific Implant Designed to Share the Fixation Space: Two-Year Clinical Outcomes - Renato Marano; Luis Fernando de Oliveira Gorla; Diogo Vasconcelos Macedo (Journal of Craniofacial Surgery, 2026)
Background: Residual paranasal concavity may persist after Le Fort I osteotomy despite adequate maxillary repositioning, limiting the aesthetic impact of orthognathic surgery. Simultaneous paranasal implant placement is rarely reported due to spatial conflict with rigid internal fixation systems and concerns regarding infraorbital nerve safety. Methods: Two patients underwent Le Fort I osteotomy combined with simultaneous placement of patient-specific paranasal implants designed through 3-dimensional virtual surgical planning (VSP) to intentionally share the anatomical space occupied by Le Fort I fixation plates. Implants were fabricated from polymethyl methacrylate (PMMA) using CAD/CAM patient-specific molds. Clinical and photographic outcomes were assessed at minimum 24-month follow-up. Results: Both patients achieved satisfactory midface projection with no postoperative complications at 24-month follow-up. No implant displacement, infraorbital nerve deficit, wound dehiscence, or plate removal was required in either case. Conclusion: A patient-specific paranasal implant designed to coexist with Le Fort I fixation hardware enables safe, effective, and stable single-stage midface augmentation during orthognathic surgery, eliminating secondary procedures over a minimum 2-year follow-up.